Modelo matemático de Holmberg en el diseño de perforación y voladura de labores de desarrollo en la mina San Benito. - Jara Ruiz, Fredy (2023)
The objective of the research work is the application of the Holmberg Mathematical Model to improve the linear advance of the development work of the San Benito S.R. mine. L., carrying out the evaluation of the unitary operation of drilling and blasting, in order to obtain good results in the linear advance. To meet the aforementioned objective, it was necessary to carry out field work. The first stage of the study is oriented to the execution of basic investigations, in order to obtain the necessary information, which will allow to evaluate the main factors of the control of drilling and blasting and to estimate the technical parameters applied to the design of drilling and blasting. In a second stage, the information obtained during the basic investigations will be integrated, in order to evaluate the drilling and blasting conditions, applying the Holmberg Mathematical Model. Through the application of the Holmberg Mathematical Model, the drilling and blasting mesh was improved in the development work of the San Benito S.R.L. mine, obtaining the following results, which are detailed below: Regular rock type: III A, RMR: 41 – 60, blasting efficiency is 95%, dip angle is 75º, advance per shot: 1.6 m., rod length: 6 feet and number of holes: 25.